2014
DOI: 10.1515/polyeng-2013-0163
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of polyamide 6/poly(2,6-dimethyl-1,4-phenylene oxide) blends by poly(styrene-co-maleic anhydride)

Abstract: The properties of polyamide 6 (PA6)/poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) blends (60/40, wt%) compatibilized by poly(styrene-co-maleic anhydride) (SMA) were studied. The addition of SMA can form an in situ copolymer, SMA-graft-PA6. The SMA-graft-PA6 copolymer actually plays a key role as a compatibilizer to improve the interface between PA6 and PPO. It was found that the effect of compatibilization resulted in improvement of the morphology, impact strength and water absorbability of PA6/PPO blends (60/4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Interestingly, the partial recovery of both values is evident for higher amounts of SMA high . These results agree with the findings of [34,35], where a similar behavior of SMA with 8 wt% MA concentration was observed for PA6/PPE. It is confirmed that SMA low reveals saturation content between 5 and 10 wt% where no further improvement of tensile properties is reported.…”
Section: Tensile Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the partial recovery of both values is evident for higher amounts of SMA high . These results agree with the findings of [34,35], where a similar behavior of SMA with 8 wt% MA concentration was observed for PA6/PPE. It is confirmed that SMA low reveals saturation content between 5 and 10 wt% where no further improvement of tensile properties is reported.…”
Section: Tensile Propertiessupporting
confidence: 92%
“…On the other hand, a physical affinity, particularly chain entanglements of the PPE and the compatibilizer backbone, are observed [28][29][30][31]. Amongst copolymer-type compatibilizers, styrene-maleic anhydride copolymers (SMA) is the most commonly used for PA6/PPE blends [32][33][34][35]. Low-priced monomers and facile synthesis via radical polymerization enable a broad commercial availability of SMA, having different MA concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the MA group of the PP- g -MA could react with the amine end group of PA and form a copolymer. 24 On the other hand, the anhydride MA group on the polyolefins can react with the hydroxyl group of EVOH, leading to an increase in the viscosity of EVOH caused by gelation (as demonstrated in Section 2.4). 25 Further, the degradation of the nanoclay surfactant produces α-olefins that can also react with hydrogen atoms available in the system, accelerating the cross-linking reactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other side, moieties of the copolymer undergo covalent bonding to the PA, either linking to the carboxylic or amino end-groups [ 32 , 33 , 34 ]. Styrene-maleic anhydride copolymer (SMA) is one of the physicochemical compatibilizers recently applied for PA/PPE blends to strengthen the interfacial interaction, morphology and mechanical performance [ 35 , 36 , 37 , 38 ]. A broad variation of different maleic anhydride (MA) concentrations allow for the tuning of interactions of the SMA with the blend partners.…”
Section: Introductionmentioning
confidence: 99%